Effectiveness of a theory-based tailored individual and family self-management education in adults with uncontrolled diabetes: A randomized controlled trial - Yohanes Andy Rias; Ratsiri Thato; Margareta Teli; Ferry Efendi (International Journal of Nursing Sciences)
Objectives: This study aimed to determine the effectiveness of an individual and family self-management (IFSM) education program on triglyceride-glucose (TyG) index, self-management, and diabetes distress among adults with uncontrolled diabetes mellitus type 2 (T2DM). Methods: A multicentre randomized controlled trial was employed. The study included 68 dyads (adults with uncontrolled T2DM and one family member) that were randomly allocated to the intervention (n = 34) and control groups (n = 34) from March to September 2024. Participants in the intervention group received an 8-week IFSM education program, whereas those in the control group received standard routine care. An automated hematology analyzer XP-100 was used to evaluate triglyceride and fasting blood glucose levels. The Diabetes Distress Scale and Diabetes Self-Management Questionnaire were used to measure diabetes distress and self-management, respectively. Results: A total of 67 participants completed the intervention. The generalized estimating equation demonstrated a significant interaction between group and time. The IFSM education intervention group had a higher diabetes self-management (β = 16.68; 95 %CI = 15.23, 18.09; P < 0.001), lower diabetes distress (β = −30.74; 95 %CI = −32.57, −28.90; P < 0.001), and lower TyG index (β = −1.97; 95 %CI = −2.41, −1.53; P < 0.001) than the control group. Conclusions: The findings documented the capacity of IFSM education to reduce TyG and diabetes distress, which could potentially escalate diabetes self-management among individuals with T2DM.